HAG (Homoharringtonine, Cytarabine, G-CSF) Regimen for the Treatment of Acute Myeloid Leukemia and Myelodysplastic Syndrome: A Meta-Analysis with 2,314 Participants. - Mixue Xie (PLoS ONE, 2016)
BACKGROUND:In China, the combination of homoharringtonine, cytarabine, and G-CSF (HAG) has been extensively applied for treatment of acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS). METHODS:We performed a meta-analysis of 2,314 patients (AML, n = 1754; MDS, n = 560) to determine the overall safety and efficacy of this regimen. RESULTS:The complete response (CR) rate of AML patients (53%) was significantly higher than that of MDS/transformed-AML patients (45%; P = 0.007). The CR rate of patients with newly diagnosed AML (62%) was significantly higher than in patients with relapsed/refractory AML (50%; P = 0.001). There were no significant difference in CR rates between elderly AML patients (54%) and all AML patients (P = 0.721). When compared with non-HAG regimens for AML/MDS induction therapy, the CR rate of patients treated with HAG was significantly higher than in treated with intensive chemotherapy (P = 0.000). No significant differences in CR rates were observed between patients treated with HAG and those treated with CAG (cytarabine, aclarubicin, G-CSF) regimens (P = 0.073). HAG regimen was well tolerated, with early death (ED) in 2%, grade IV myelosurrpression in 52% and infection in 50%. Reports of ED and rates of myelosuppression were reduced as compared with intensive chemotherapy (P = 0.000 and P = 0.000, respectively). CONCLUSION:The HAG regimen is an effective and safe regimen for the treatment of AML and MDS, and appears to be more effective and better tolerated than intensive chemotherapy. Future randomized controlled trials and further meta-analyses are strongly needed to confirm its efficacy and safety, especially in comparison with intensive chemotherapy.